Proposed research programme and research protocols for 1986-1989 - Bekure, S.; Leeuw, P.N. de; Pasha, I.K.O.; Tessema, S.; Woie, B.M.; Maranga, E.K.; Shaabani, S.B. (International Livestock Centre for Africa, 1986)
Research agenda for ILCA's Kenya programme, including details of objectives, programme of work, time schedule, data evaluation procedures and expected benefits for each research component to improve livestock productivity of pastoralists and systems research to improve mixed farming systems, both in the semi-arid rangelands. Gives background information on the characteristic and constraints of both farming systems.